Optimal variable bank capital requirements - Ragna Alstadheim (Norges Bank, 2021)
The purpose of the "counter-cyclical capital buffer" (buffer) is to dampen procyclicality in the financial system, absorb capital losses and prevent a credit crunch during recessions. In this paper, a stylized analytical expression for optimal buffer policy is presented. Results are derived within a minimalist model framework, useful for a transparent presentation of how authorities' preferences and structural parameters have implications for optimal buffer policy. In the model, there is a risk of a financial crisis, and an ex ante higher buffer may counteract the effects of it on the economy. The buffer also affects output in the short term, and here the difference between banks' actual capital coverage ratio and capital requirements plays a role. Under quite general conditions, authorities will want to lower the buffer and allow banks to be less well capitalized today if the output gap is negative. The model illustrates that unless authorities care also about a stable bank capital coverage ratio (in addition to output stabilization and the costs of crisis), optimal policy may prescribe a very volatile buffer. In particular, that is the case if the effect of the buffer on output is weak. This result highlights the importance of learning more about the effects of buffer policy in order to achieve good policy design.
hdl:11250/2835497
Keywords: E32; E44; E61; G21; G28; 330; CCyB; Optimal policy; Crisis